(3GdJhVjM aj Md ZhGeV GdJfbjMs - (3YHjO Gdgd Hf eSYhO GdeMHhi GdHNGQjs; (3UOQ GdTQjYI GdGUZQ , YHjOGddg Hf eSYhO Hf eMehO Hf CMeO GdeMHhHj,J (B747 (3g` s
(3ChdgG (B:s
(3MGeOkG ddg ChdkG KGfjkG hHYO aEf GdYHO GdeJhSd Edi Gddg JYGdi jbhd deG habfi Gddg JYGdi HJCdja cJGH JfbjM GdCUhd CQOJ Cf CTQM eTcdGJg s
(3BNQgG (B:s
(3adG jchf HefRdI bJd GdfaS HNdGa RfG GdQLd aEfg HefRdI GdbJd dCfg bWY GdfSH hGddg hdi GdYUeI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B246s
Keywords: (3CUhd Gdabgs